The Impact Of Islamic Leadership On Employee Satisfaction On Syariah Banking Institutions In Medan City - Raihanah Daulay; Dedek Marlina (Proceeding International Seminar of Islamic Studies, 2019)
A tough challenge that leaders often have to face is how to move their subordinates to always want and be willing to exert his or her best skills for the sake of their group or organization. The relationship between employees and leaders is very important in increasing productivity so that it will give job satisfaction. For that the leader must have the nature of trust, professional and also has the nature of responsibility. Leadership is not arbitrariness to act, but the authority serves to nurturing and to do it as justly. Each of you is a leader, and you will be held accountable for his leadership (H. R. Bukhori). The purpose of this research is to know how Islamic leadership towards employee satisfaction in Syariah banking institutions in Medan city.The study approach uses associative research. Data collection techniques using polls and interviews. The result of a correlation analysis shows that Islamic leadership affects job satisfaction. The value of Thitung 4.081 1.998 Ttabel, it shows there is a significant level of Islamic leadership towards job satisfaction. The value of coefficient of determination is 0.209 or 20.9%. This means that leadership affects 20.9% of job satisfaction, the rest are influenced by unresearched factors.